Adapting work to the worker: The evolving EU legal framework on accommodating worker diversity. Issue 2 (June 2018) - Bell, Mark
The changing profile of the European workforce creates pressure to adapt the working environment in order to accommodate worker diversity, such as that related to disability, religious practice or caring responsibilities. There is an ongoing debate within equality law on the extent to which law should require employers to provide such accommodation. This article examines the rationales that justify legal intervention and maps out various ways in which European Union legislation already requires employers to accommodate worker diversity. It identifies three types of accommodation duty: protective, substantive and procedural. The article argues that the debate can be enhanced by looking beyond the confines of equality law and drawing connections with a wider agenda for labour market reform. A better understanding of the different types of accommodation duty helps to expand the debate beyond a narrow focus on whether the duty of reasonable accommodation for workers with disabilities should be extended to other discrimination grounds.